Development of Digital Comic Media IPAS Based on LVEP to Enhance Global Diversity Character in Grade V Elementary School - Ira Setyawati; An-Nisa Apriani; Indah Perdana Sari; Ruwet Rusiyono (DAS Institute, 2026)
This study aims to create a digital comic medium utilizing the Living Values Education Program (LVEP) to foster global diversity character in fifth-grade elementary students. The objective is to nurture students' potential in personality, morals, skills, and spiritual aspects. Introduced by Indonesia’s Minister of Education and Culture, Nadiem Makarim, in April 2021, the